Neurological repercussions of insomnia: A integrative review (Research, Society and Development, 2022)
Objective: To present the main short, medium and long-term neurological repercussions of insomnia on the human body. Methodology: An integrative review was carried out in the databases indexed to Google Scholar and PUBMED, using as inclusion criteria articles published between 2009 and 2022, in English and Portuguese, and as exclusion criteria, duplicate and unrelated articles with the theme. Results: 23 articles were used, in which it was possible to identify the relationship between insomnia and the development of various diseases at all stages of life and in damage to school activities, work and even social relationships, cause metabolic syndrome disorders and cardiovascular disease and providing future neurodegenerative diseases. Final Considerations: It was possible to identify that insomnia has great potential to impact the individual's quality of life or to aggravate other diseases, as it is related to the development of various somatic and psychosocial pathologies, including anxiety, depression, memory problems, diseases chronic diseases such as cardiovascular diseases, hypertension, diabetes, cancer and decreased quality of life.